Effect of Variety and Seed Rate on Yield Performance of Mungbean Under Strip Tillage System - Rahman, Md Moshiur; Zahan, Taslima; Ali, MS; Begum, M; Bell, RW (Bangladesh Agronomy Journal, 2016)
A study was conducted at Bangladesh Agricultural University, Mymensingh during March-June, 2013 to evaluate the performance of mungbean varieties and to determine the optimum seed rate under strip tillage system. Three mungbean varieties (BARI Mung-6, Binamung-5 and Binamung-8) were tested against five seeding rates (20, 25, 30, 35 and 40 kg ha-1). The experiment was laid out in splitplot design with three replications. The study revealed that variety and seed rate had significant effect on plant population, pods plant-1, pod length, seeds pod-1, seed yield and stover yield of mungbean. The highest seed yield was obtained from Bina mung-5 at 35 kg seed ha-1 while the highest stover yield was obtained from 40 kg seed ha-1. For BARI Mung-6 and Binamung-8, 35 kg seed ha-1 also provided higher seed yield than other seeding rates. Nevertheless, the lowest seed and stover yields were obtained from Bina mung-8 with 20 kg seed ha-1. Therefore, the study concluded that machine seeding of mungbean at 35 kg seed ha-1 ensure optimum seed yield for tested varieties under strip tillage system and cultivation of Bina mung- 5 at 35 kg seed ha-1 can produce the maximum seed yield under this system. Bangladesh Agron. J. 2016, 19(1): 81-86